CPWF Volta V5 Main Message Poster - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2013)
High-quality scientific research, grounded in regular engagement with stakeholders, will improve the uptake of research results and lead to outcomes.